Pemanfaatan Limbah Serbuk Kayu dan Fly-Ash Sebagai Bahan Tambah Pembuatan Genteng Beton Eco-Friendly - Ahcmad Faruk Faqrudin; Syaiful Kharis Setiawan; Riza Susanti; Puji Widodo (Universitas Diponegoro, 2023)
Some roofs in Indonesia still use concrete tiles because they are expensive and heavy. Indonesia is also the country that produces the most wood and coal in the world, this will cause sawdust and fly ash waste. Therefore, research was carried out aimed at using sawdust and fly-ash waste as mixed materials and trying to make lighter concrete roof tiles. So that in its use it can lighten roof construction and also utilize waste so that concrete roof tiles become more economical but have quality that meets SNI. The method used is an experimental method, with a cement and sand mixture composition of 1: 3 and using 4 variations of test objects, namely for sawdust variation A, 0%; B, 25%; C, 0%; D, 25% of the sand weight while for fly ash variation A, 0%; B, 0%; C, 25%; D, 25% of cement weight. This test includes appearance properties, size, flatness, bending load, water absorption and seepage. The average bending load results in variations A = 170,632 kg, B = 168,933 kg, C = 195,446 kg, D = 179,812 kg. For the average water absorption test results for variations A = 9.44%, B = 10.07%, C = 6.12%, D = 8.13%. The use of sawdust can reduce flexural strength and increase water absorption and the addition of fly ash will increase flexural strength and reduce water absorption compared to normal concrete roof tiles. Therefore, it can be concluded that concrete roof tiles with the addition of sawdust and fly ash are better, economical and lighter than concrete roof tiles without added materials and still meet SNI.